Locus-Specific Rescue of GluRϵ1 NMDA Receptors in Mutant Mice Identifies the Brain Regions Important for Morphine Tolerance and Dependence - Inoue, Makoto (J Neurosci, 2003)
Tolerance and physical dependence caused by chronic treatment of narcotics are good models to study basic neuronal plasticity. Activation of the NMDA subtype of the glutamate receptor has been implicated as an anti-opioid system in the development of morphine analgesic tolerance and dependence. The present study examines the specific role of the ϵ1 subunit of the NMDA receptor using mice lacking the gene encoding ϵ1 subunit of the NMDA receptor (GluRϵ1(-/-) mice). GluRϵ1(-/-) mice showed significant enhancement and prolongation of morphine anti-nociception, compared with wild-type GluRϵ1(+)(/)(+) mice. GluRϵ1(-/-) mice also showed a marked loss of the analgesic tolerance after repeated morphine treatments. In C57BL/6J mice treated with chronic morphine after tolerance paradigm, the GluRϵ1 protein expression significantly increased in periaqueductal gray matter (PAG), ventral tegmental area (VTA) and nucleus accumbens (NAc), but not amygdala or hippocampus. The rescue of GluRϵ1 protein by electroporation into the PAG and VTA, but not NAc of GluRϵ1(-/-) mice significantly reversed morphine analgesic tolerance liability. Similar attempts were also performed in the naloxone-precipitated physical dependence paradigm. GluRϵ1(-/-) mice showed marked loss of typical withdrawal abstinence behaviors, and significant enhancement of GluRϵ1 protein expression was only observed in NAc by chronic morphine treatments after dependence paradigm. The rescue of GluRϵ1 protein by electroporation into the NAc of GluRϵ1(-/-) mice significantly reversed the loss of abstinence behaviors. These findings suggest that GluRϵ1 has locus-specific roles in the development of morphine analgesic tolerance and physical dependence.